EKSPLORASI HAMBATAN ADOPSI DIGITAL MARKETING PADA UMKM DI JAWA TIMUR - Lianto, Catherine (Jurnal Bisnis Terapan, 2026)
This exploratory study aims to examine the barriers to the adoption of Digital Marketing (DM) among Small and Medium Enterprises (SMEs) in East Java, a province with the largest number of SMEs in Indonesia. The adoption of DM is considered a crucial marketing strategy to enhance competitiveness and expand market reach in the digital era. However, SMEs in East Java continue to face various challenges, including limited access to technology, low digital literacy, and insufficient understanding of the benefits of DM. To analyze these barriers, this study employs a qualitative exploratory approach, with data collected through in-depth interviews involving SME owners, academics, and practitioners with experience in DM implementation. The collected data were analyzed using NVivo software through open, axial, and selective coding processes to identify key themes representing barriers to DM adoption. The findings indicate that the dominant barriers are internal factors, particularly limitations in human resource competencies and digital capabilities. In addition, external factors related to government regulations also hinder adoption, especially due to policy complexity and inadequate socialization. Continuous training and coaching are identified as the most expected strategies to overcome these barriers.